Determinants of Toddler Toilet Training Readiness in the Kenjeran Community Health Center in Surabaya - Kartika Fatmawati; Yuni Sufyanti Arief; Iqlima Dwi Kurnia (Pediomaternal Nursing Journal, 2020)
Introduction: Toilet training for children is an attempt to train children to control bowel movements and urination. Besides, children are encouraged to be able to defecate and urinate in the specified place. The success of toilet training depends on the readiness of the child and family. This study aims to determine the factors that affect toilet training readiness for toddlers.Methods: The research design used is descriptive analysis, with a cross-sectional approach. The population at Kenjeran Community Health Center is 2.755 toddlers, and the sample used in this study is 25 toddlers with purposive sampling. The instrument used in this study was a children's toilet training questionnaire. Data were analyzed using the crosstab and chi-square analysis.Results: This study showed a relationship between the child's age and the child's sex with the readiness of the child's toilet training with p = 0.00 (α = 0.05).Conclusion: Nurses as health workers are expected to be educators to parents about the importance of toilet training in children by taking into account both physical, psychological, and environmental aspects in supporting the process of toilet training.